Az etnikai kapcsolati tőke földrajza - Kovály Katalin; Коваль Катерина (Gondolat Kiadó, 2024)
Jelen kötet ukrajnai vállalkozók körében végzett kutatás alapján ismerteti az etnikai kapcsolati tőke, a transznacionális kötődések vállalkozásokban betöltött szerepét és azok földrajzi sajátosságait. Továbbá pillanatfelvételt nyújt az orosz–ukrán háború okozta társadalmi-gazdasági változásokról Kárpátalján. A monográfia a magyar nyelvű geográfián belül újszerű kutatást mutat be, amely empirikus vizsgálat segítségével, komparatív módon tárja fel az egyes autochton és allochton közösségek általi tőkebefektetések és az etnikai viszonyrendszerek korrelációit, az etnicitás és a kapcsolati tőke összefüggéseinek földrajzi szempontú elemzésével.

Резюме. У монографії, на основі емпіричних досліджень, проведених серед вітчизняних та іноземних підприємців Закарпаття та українських підприємців-мігрантів, які ведуть свою діяльність на території Чехії, простежено взаємозв’язок між інвестиціями та етнічним соціальним капіталом. Окрему увагу приділено просторовому розташуванню їхнього бізнесу та суспільно-географічним аспектам. Метою дослідження було проаналізувати, яку роль відіграє у певних бізнесах – що функціонують у різних підприємницьких середовищах та пов’язані з окремими алохтонними та автохтонними етнічними групами – етнічний соціальний капітал, зокрема у діяльності та просторовій організації таких бізнесів.

Abstract. This monograph presents the role of ethnic social capital in the life of enterprises, with special emphasis on their spatial organization, based on the research carried out in two Central and Eastern European regions (Transcarpathia and the Czech Republic). The aim of the research was to identify the role of informal and formal ethnic relationships in the functioning and spatial organization of entrepreneurial activities, operating in different countries, run by different ethnic groups in disparate economic environments. My further goal was to introduce the term ethnic social capital in Hungarian Geography. The investigation is a novum in the Hungarian social geography, which is based on thorough empirical research, and offers a comparative analysis on the correlation between the capital investments implemented by autochthon and allochthon communities and the ethnic relation systems, by analyzing the relationship between ethnicity and social capital from geographical point of view. The book also reflects on the socio-economic consequences of the Russo-Ukrainian war in Transcarpathia.
Ukrajnai vállalkozók a transznacionalitás útján
https://opac3.brff.monguz.hu/hu/record/-/record/bibMOK09105926
Keywords: Ukrajna; tőke; etnikai kapcsolatok; vállalkozás; vállalkozók; földrajz; Kárpátalja